Building Career PATHS (Postschool Achievement Through Higher Skills) for Young Women With Disabilities. Issue 4 (December 2013) - Lindstrom, Lauren; Doren, Bonnie; Post, Cindy; Lombardi, Allison
<x xml:space="preserve">Abstract</x> The PATHS (Postschool Achievement Through Higher Skills) curriculum is designed to address the career development needs of young women with disabilities and other barriers. Participants (N = 110) in a pilot test of the curriculum showed increases in vocational self‐efficacy, social efficacy, and awareness of disability/gender issues related to career planning, whereas those in the comparison group did not make similar gains. Qualitative findings from focus groups (N = 68) revealed that PATHS participants improved in self‐confidence, self‐awareness, ability to identify strengths, knowledge of multiple career options, and the capacity to set goals and plan for future careers.